Beyond "Lack of Political Will": Elaborating Political Economy Concepts to Advance "Thinking and Working Politically"; Comment on "Health Coverage and Financial Protection in Uganda: A Political Economy Perspective" - Aloysius Ssennyonjo (Kerman University of Medical Sciences, 2023)
Political economy analysis (PEA) has been advanced as critical to understanding the political dimensions of policy change processes. However, political economy (PE) is not a theory on its own but draws on several concepts. Nannini et al, in concert with other scholars, emphasise that politics is characterised by conflict, contestation and negotiation over interests, ideas and power as various agents attempt to influence their context. This commentary reflects how Nannini et al wrestled with these PEA concepts - summarised in their conceptual framework used for PEA of the Ugandan case study on financial risk protection reforms. The central premise is that a common understanding of the PEA concepts (mainly structure-agency interactions, ideas, interests, institutions and power) forms a basis for strategies to advance thinking and working politically. Consequently, I generate several insights into how we can promote politically informed approaches to designing, implementing and evaluating policy reforms and development efforts.